IVF Births and Pregnancies: An Exploration of Two Methods of Assessment Using Life-Table Analysis - Deonandan, Raywat (Université d'Ottawa | University of Ottawa, 2001)
Purpose: Our purpose was to explore two methods of expressing the performance of IVF programs. Methods: Using life-table methods, hazard and cure rates and a “monthly fecundability rate” were calculated for an Ontario IVF clinic. The rates were evaluated for their meaningfulness as indicators of the clinic’s performance. Results and Conclusions: While the hazard rate describes monthly fertility among those who will eventually become pregnant, the fecundability rate describes fertility for all patients who enter the program, making it the more appropriate index for program comparisons. However, from a prospective patient’s perspective, both methods are valid indices for summarizing a program’s performance.
Keywords: IVF; cure rate; fecundability rate; hazard rate; life-table analysis; survival analysis